The Effect of Adding Rosemary Powder on the Physiological and Biochemical Characteristics of Blood and Antioxidant Status of Female Quails - Ameen, Gulala W.; Noaman, H. A.; Mohammed, Diyar Jaafar (CV. Literasi Indonesia, 2025)
This study was conducted at the poultry farm of the Animal Production Department, College of Agriculture / University of Kirkuk, during the period from 01/02/2023 to 24/2/2023, to determine the effect of adding rosemary powder on the physiological and biochemical characteristics of blood and the status of antioxidants in the blood serum of female quails. 64 female Japanese quails, eight weeks old, were used. The birds were randomly distributed into four treatments, each treatment had four replicates, and each replicate had four female Japanese quails. The birds were fed free feed, and the treatments were distributed as follows: The first treatment was a control treatment, i.e., without addition, the second treatment added 0.25% rosemary powder, the third treatment added 0.50% rosemary powder, and the fourth treatment added 0.75% rosemary powder. The results of the statistical analysis led to: The results led to an improvement in the percentage of antioxidants in the blood serum, as well as a significant decrease in the percentage of blood fats (cholesterol HDL-LDL-VLDL and also in the percentage of liver enzymes compared to the control treatment.